ANALISIS PERBANDINGAN DESAIN DINDING PENAHAN TANAH DENGAN VARIASI KONSISTENSI TANAH ASLI DAN TANAH TIMBUNAN - Valencia Renata; Aniek Prihatiningsih (JMTS: Jurnal Mitra Teknik Sipil, 2022)
Retaining wall is a structure that is built to retain inclined land or on land where its stability is easilydisturbed. Retaining wall structures are used to withstand lateral soil pressures caused by embankment soilor unstable original soil due to topographic conditions. However, it is also common to find cases oflandslides at project sites where retaining walls have been installed. The failure of this retaining wall isgenerally caused by a design that is not in accordance with the soil conditions at th e project site or due toexternal factors that are not considered in the planning process. Therefore, in designing retaining walls,the parameters and properties of the soil, both original soil and embankment soil, are important factors tobe considered. The purpose of this study is to compare 5 designs of gravity retaining walls in 2 soilconditions that have different consistency of original soil and embankment soil. The design of retainingwalls is checked for shear stability, overturning, soil bearing capacity, global failure, and deformation.Calculation of soil pressure is calculated using conservative method with Rankine Theory and thecalculation of stability to the failure of the bearing capacity of the soil is calculated based on the Hansenand Vesic equations based on soil characteristics and technical data (c and ϕ). Analysis of shear stability,overturning, and bearing capacity of retaining walls was carried out using conventional method , whilestability calculations against global failure and deformation were carried out u sing the finite elementmethod-based program using CPT data and SPT value on project located in Bukit Asam area, Palembang.and Buleleng Regency, Bali.